Hashing into Hessian curves. (1st January 2014) - Farashahi, Reza Rezaeian
We propose an encoding function from the elements of the finite field F q into points on a Hessian curve. Next, we present an injective encoding function from the set of all positive integers less than or equal to ℓ into points on a Hessian curve over Fq with odd q and ℓ = ( q - 1)/2. We also present an injective encoding function from the bit strings of length k 􀀀 1 into points on a Hessian curve over the binary finite field F 2 k .